Advancing tree genomics to future proof next generation orchard production - Kerr, Stephanie C.; Shehnaz, Saiyara; Paudel, Lucky; Manivannan, Mekaladevi S.; Shaw, Lindsay M.; Johnson, Amanda; Velasquez, Jose Teodoro J.; Tanurdžić, Miloš; Cazzonelli, Christopher I.; Varkonyi-Gasic, Erika; Prentis, Peter J. (Frontiers in Plant Science, 2024)
The challenges facing tree orchard production in the coming years will be largely driven by changes in the climate affecting the sustainability of farming practices in specific geographical regions. Identifying key traits that enable tree crops to modify their growth to varying environmental conditions and taking advantage of new crop improvement opportunities and technologies will ensure the tree crop industry remains viable and profitable into the future. In this review article we 1) outline climate and sustainability challenges relevant to horticultural tree crop industries, 2) describe key tree crop traits targeted for improvement in agroecosystem productivity and resilience to environmental change, and 3) discuss existing and emerging genomic technologies that provide opportunities for industries to future proof the next generation of orchards.